Anti-CRISPR-mediated control of gene editing and synthetic circuits in eukaryotic cells - Muneaki Nakamura (Nature Portfolio, 2019)
Anti-CRISPR proteins derived from phage can abrogate CRISPR activity. The authors repurpose these molecules for demonstrating genomic write-protection and pre-programmed gene expression circuits.